A comparative study of satisfaction evaluation between students of mid-rise and high-rise student housing. Issue 7 (6th December 2020) - Nazarpour, Mohammad-Taghi; Norouzian-Maleki, Saeid
Abstract : Purpose: The purpose of the current research is to examine the student's residential satisfaction (SRS) of dormitories in Tehran and Shiraz. Providing homes for non-native students is considered as one of the key issues in university development. Design/methodology/approach: A combination of qualitative and quantitative measurements (mixed methods) was used to compare some of the design features between middle-rise and high-rise student housing. Questionnaire forms were distributed between male students of "Shahid Beheshti University" and "Shiraz University" dormitories. Cluster sampling is done among residential blocks in each university. Students assessed perceived attributes of dormitories by indicating their satisfaction from different categories. The obtained data were analysed by SPSS software and the Mann-Whitney test. Findings: Findings show that although in comparing two samples with only some of the criteria, Shahid Beheshti University dormitory was ranked higher, generally Shiraz University dormitory was more successful in meeting resident's satisfaction. Among the physical features, the pleasant views and landscape are important components which are related to aesthetic preferences. Research limitations/implications: More research examining student/environment interactions is needed to pay close attention to cultural aspects. The consideration of culturally diverse individuals in the assessment may also provide valuable insight into the students' residential satisfaction. Practical implications: In sum, the design implications resulting from the data analysis act as a step toward an evidence-based design approach. Housing designers can integrate the research findings with design solutions. They take active part in the design process by developing new methodologies to highlight their role in creating high-quality student housing. Originality/value: The relationship between students and their residential environment has been a mainstream topic in environmental psychology. Some previous studies have focused on socio-demographic characteristics, whereas others have dealt with the physical characteristics of the student housing that affect SRS.